2018
DOI: 10.1055/s-0038-1642600
|View full text |Cite
|
Sign up to set email alerts
|

Lipoprotein Profile Modifications during Gestation: A Current Approach to Cardiovascular risk surrogate markers and Maternal-fetal Unit Complications

Abstract: Several changes occur in lipid metabolism during gestation due to hormonal and metabolic changes, which are essential to satisfy the nutritional demands of the maternal-fetal unit development. The gestation shows two distinct periods that begin with fat accumulation, mainly in maternal adipose tissue, and the late phase, characterized by accelerated catabolism, with the increase of fatty acids in the circulation that causes hyperlipidemia, especially the one characterized as hypertriglyceridemia. Maternal hype… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 64 publications
(120 reference statements)
0
4
0
Order By: Relevance
“…The prevalence of GDM, preterm birth and low birth weight differs by ethnicity, and we and others have reported ethnic differences in foetal growth [ 24 ]. Adverse lipid profiles are strongly related to cardiometabolic diseases, but of note, women with pregnancy complications like preeclampsia and GDM are also at higher risk of later cardiovascular disease (CVD) and type 2 diabetes [ 21 , 25 27 ]. Ethnic differences in concentrations of lipids and lipoproteins outside pregnancy are well documented, with women of South Asian origin displaying higher triglycerides, lower HDL-cholesterol and more small, dense LDL-cholesterol particles related to insulin resistance, compared with women of Western European origin [ 28 , 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of GDM, preterm birth and low birth weight differs by ethnicity, and we and others have reported ethnic differences in foetal growth [ 24 ]. Adverse lipid profiles are strongly related to cardiometabolic diseases, but of note, women with pregnancy complications like preeclampsia and GDM are also at higher risk of later cardiovascular disease (CVD) and type 2 diabetes [ 21 , 25 27 ]. Ethnic differences in concentrations of lipids and lipoproteins outside pregnancy are well documented, with women of South Asian origin displaying higher triglycerides, lower HDL-cholesterol and more small, dense LDL-cholesterol particles related to insulin resistance, compared with women of Western European origin [ 28 , 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…In a case-control study carried out in Dubai, which aimed to determine the association between dyslipidemia, overweight and the risk of PE, found that, mainly, hypertriglyceridemia was highly correlated with overweight in pregnancies with the disease 4 . In other study, report that in obese pregnant women dyslipidemia is more accentuated which could be justified by the fact that overweight pregnant women have greater difficulties in adapting to the metabolic change characteristic of the gestational period 6 .…”
Section: Discussionmentioning
confidence: 89%
“…A meta-analysis that evaluated cohort studies concluded that hypertriglyceridemia precedes the development of PE 3 , which is caused by the hepatic production of very low density lipoproteins (VLDL) rich in TG due to their lipolysis in adipocytes, and by the decrease in VLDL clearence due to the decrease in lipoprotein lipase (LPL) and liver lipase, being the main lipid manifestation observed in pregnancies with dyslipidemia 6 . In this study pregnant women with PE presented higher mean TG levels when compared with pregnant women without the disease, similar to the findings by Jamal et al 14 who found an average with pregnant women with the disease in Multan.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation